Implementasi Pendekatan Sistem dalam Meningkatkan Manajemen Sekolah SMA Negeri 7 Binjai - M, Maulidayani; Simangunsong, Arimbi Syahkila; Sembiring, Ari Wibowo; Sibarani, Lola Amalia; Ramadhan, Syahpan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Implementing a systems approach in improving school management is an effort that aims to design, manage and optimize all components involved in school operations as an integrated system. This approach allows the school to operate as an integrated entity, focusing on various interrelated components.This research uses a qualitative descriptive research method. Data collection instrument namely through (1) observation, (2) interviews and (3) documentation. The implementation of a systems approach in improving the management of SMA Negeri 7 Binjai shows that this approach has great potential to bring positive changes in school management. By implementing a systems approach, schools can better manage resources, teachers, and students to improve the quality of education and learning outcomes